2013
DOI: 10.1021/ma401478t
|View full text |Cite
|
Sign up to set email alerts
|

Toughening Epoxy Thermosets with Block Ionomers: The Role of Phase Domain Size

Abstract: Herein we report a novel approach to toughen epoxy thermosets using a block ionomer, i.e., sulfonated polystyrene-block-poly­(ethylene-co-butylene)-block-polystyrene (SSEBS). SSEBS was synthesized by sulfonation of SEBS with 67 wt % polystyrene (PS). Phase morphology of the epoxy/SSEBS blends can be controlled at either nanometer or micrometer scale by simply adjusting the sulfonation degree of SSEBS. It has been found that there exists a critical degree of sulfonation (10.8 mol %) forming nanostructures in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…The research activities on ionomer are gaining interests day by day. Ionomer is used for toughening of epoxy thermosets using block ionomers, as shape memory material and self‐healing material under high‐energy impact conditions . The antibacterial activity sulfonated polystyrene (SPS) and silver nanocomposites (SPS/Ag) was also explored.…”
Section: Introductionmentioning
confidence: 99%
“…The research activities on ionomer are gaining interests day by day. Ionomer is used for toughening of epoxy thermosets using block ionomers, as shape memory material and self‐healing material under high‐energy impact conditions . The antibacterial activity sulfonated polystyrene (SPS) and silver nanocomposites (SPS/Ag) was also explored.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that high loadings of conductive fillers are usually required to achieve high electrical conductivity which can degrade the stretchability of the composites and leads to lower processability. Moreover, it was demonstrated that the strain sensitivity of the composites increases upon decreasing the conductive filler content and the highest sensitivity was found to occur at a filler concentration near the percolation threshold . Therefore, the conductivity/sensitivity, stretchability/processability dilemma should be taken into account in the design of conductive polymer composites.…”
Section: Materials Designsmentioning
confidence: 99%
“…hydrogen bonding), which have been reported by others. 12,20 For BCP/TDE-85/DDS blends, oxygen atoms of epoxy-philic blocks (e.g., PEG) can form hydrogen bonding with the amino groups of DDS (or with hydroxyl groups inevitably formed from TDE-85 via ring-opening reaction during melt blending), which can result in miscibility. Aer curing, the nonreactive EPE80-modied thermoset becomes obscure (Fig.…”
Section: Phase Behaviourmentioning
confidence: 99%
“…The most common toughening way is incorporating a second phase, such as elastomers, 1-3 thermoplastic polymers, 4-6 nanoparticles 7-9 and block copolymers (BCPs). [10][11][12][13][14][15][16] For elastomers or thermoplastic polymers, it usually requires an optimizing loading of ca. 10-20 wt% to obtain a desirable toughening effect.…”
Section: Introductionmentioning
confidence: 99%